Idiopathic Pulmonary Fibrosis Mimics Pulmonary Malignancy: A Case Report - Ketut Wiswa Wikrama; Carolus Boromeus Tabuni; Ananda Digdoyo; Putu Nanda Pratama Putra; Petra Gusti Parikesit; Sutaryanu Darmoredjo (CV. Inara, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease characterized by extracellular matrix accumulation, often mimicking pulmonary malignancy in clinical and radiological aspects. Early and accurate diagnosis remains a challenge. Objective: To report a case of IPF presenting with hemoptysis and radiological features suggestive of malignancy, highlighting diagnostic complexities. Methods: This qualitative case study involved detailed clinical, radiological, and histopathological examination of a 60-year-old female patient. Data were collected through medical records, CT imaging, biopsies, and interviews. Thematic content analysis ensured rigorous interpretation. Results: Radiologic findings indicated suspicious masses bilaterally, yet histopathology confirmed pulmonary fibrosis without malignancy. This underscores the overlap in presentation and diagnostic ambiguity between IPF and lung cancer. Conclusion: Multimodal diagnostic approaches combining imaging and biopsy are essential to distinguish IPF from malignancy and to guide treatment. Increased clinician awareness and multidisciplinary collaboration enhance diagnostic accuracy and prognosis. Further research with larger samples is recommended to improve non-invasive diagnostic tools.